Effect of the Slowest Heating Zone Movement on Thermophysical Kinetics in Food Systems - Vladimir V. Kondratenko; Natalia E. Posokina; Anna I. Zakharova; Aleksei A. Korolev; Galina P. Pokudina (Техника и технология пищевых производств)
The slowest heating zone tends to move about in food systems with convective and predominantly convective heat transfer. If the thermocouple follows the movement, the process lethality differs from the value precalculated for a fixed thermocouple location. Hence, the heat treatment modes depend on the movement of the slowest heating zone, which should be taken into account before planning food system processes. This research aimed at identifying a statistically significant difference between lethality for fixed and moving slowest heating zones in various food systems. The study involved four homophasic and heterophasic model food systems. Food System 1 was heterophase, with a dispersed phase not involved in convection and a liquid dispersion medium of aqueous solution with 1.5% sucrose and 1.5% NaCl. Food System 2 was heterophase, with a dispersed phase not involved in convection and a liquid dispersion medium of 11% aqueous sucrose solution. Food System 3 was represented by homophase reconstituted clarified baby-food apple juice with 11.2% soluble solids. Food System 4 was a heterophase model system, represented by reconstituted baby-food apple juice with pulp and 11.2% soluble solids with a dispersed phase involved in convection. The temperature changes were monitored using the E-ValPro multichannel system and the SSA-TS model temperature sensors. The temperature sensors were fixed inside the jar with the food system. Food System 1 showed no significant differences in lethality. Other model systems had sterilization temperature intervals when the difference in lethality was statistically significant. However, this difference was very small for Food Systems 2 and 3. The largest difference belonged to Food System 4, where the dispersed phase was involved in the convective flow. In this research, a statistically significant difference in lethality for fixed and moving slowest heating zones occurred only in heterophase food systems with convective and predominantly convective heat exchange, where the dispersed phase was involved in the convection flow. This fact must be taken into account when identifying heat treatment modes for such food systems.